Wood evaluation by using ultrasonic technique / Nur Hani Che Halim. - Che Halim, Nur Hani (2013)
This report is to study the ultrasonic wave velocity and orthotopic direction with respect to different moisture content in wood. Samples are cut down from Aquilaria species tree. Eight different samples with 3cm X 2cm X 9cm dimension are constructed from the cross-sectional area of wood. The samples are dried by using spotlight in order to ensure the sample properly dried. Ultrasonic velocity technique is used to determine the velocity wave propagate in wood sample after dried. There are three directions, parallel, perpendicular, and tangential to the wood grain have being inspected. In order to obtain 9 % and. 15 % of MC, the samples are immersed in water in certain period; 2 hour produces 9% MC whereas for 15% MC time needed is 5-6 hours, velocity wave is measured by using ultrasonic testing technique. From the result obtained, dried sample produces the higher velocity wave and parallel direction measured is the best technique to be used other than perpendicular and tangential. It can be demonstrated that the velocity is sensitive to changes in moisture content of wood samples. Results indicated the moisture content as the main factor in this study.